Pengaruh Kualitas Produk dan Promosi terhadap Keputusan Pembelian Golden Farm French Fries pada PT. Sukanda Djaya Medan - Sitompul, Melva Melany (JEBIM Prima, 2020)
Marketing activities in the company are the main thing in keeping the company able to provide products in accordance with customer expectations. The company’s ability to provide products that meet customers expectations will certainly be a value for customers in giving trust to the company and continuously buying these products.This of course will also make the income owned by the company able to increase.Purchasing decisions are decisions that are given determining which product to choose and to buy.Purchasing decisions are important when the company is able to maintain customer confidence properly, it will create repeat purchases from consumers which of course will make profits for the company.Product quality is a product’s ability to meet consumer expactations. High product quality will give a good impression to consumers when consuming these products. All consumers expect good quality when buying a product. Product quality factors are closely related to consumer choice. Promotion is an activity to introduce the features of product to cunsumers.Promotion is very important in managing and supporting companies in selling the products they have. With the promotion the company will be better able to introduce products to consumers in the company.